Synthesis and Deprotection of Cyclic Oxalate - Kim, Yun-Young (Asian Journal of Chemistry, 2014)
As a new protective group for diols, cyclic oxalates [trans-1,2-cyclo-hexane diol 1,2-oxalate (1), 1,2:5,6-di-O-isopropylidene-D-mannitol 3,4-oxalate (2) and 1,2-propanediol 1,2-oxalate (3)] were synthesized by using oxalyl chloride, ethyloxalyl chloride, diethyl oxalate and oxalic acid. Cyclic oxalates were readily cleaved to the corresponding diols by various bases such as sodium methoxide, potassium carbonate, 1 % sodium hydroxide, triethylamine and lithium aluminium hydride, but were stable in acid.